2012
DOI: 10.1242/jeb.069245
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms contributing to the dopamine induction of crawl-like bursting in leech motoneurons

Abstract: SUMMARY Dopamine (DA) activates fictive crawling behavior in the medicinal leech. To identify the cellular mechanisms underlying this activation at the level of crawl-specific motoneuronal bursting, we targeted potential cAMP-dependent events that are often activated through DA 1 -like receptor signaling pathways. We found that isolated ganglia produced crawl-like motoneuron bursting after bath application of phosphodiesterase inhibitors (PDIs) that upregulated cAMP. This bursting persisted in salines in which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 65 publications
1
13
0
1
Order By: Relevance
“…6B). This principle has been well documented in a variety of invertebrate (Crisp et al, 2012; Dickinson and Nagy, 1983; Khorkova and Golowasch, 2007; Ramirez and Pearson, 1991a,b; Zhao and Golowasch, 2012) and other mammalian networks (Kolaj et al, 2007; Mrejeru et al, 2011; Tsuruyama et al, 2013). Within the respiratory network, multiple neuromodulators, such as serotonin, norepinephrine, acetylcholine, or substance P,can alter the distribution of these activities (Doi and Ramirez, 2008; Ramirez et al, 2012; Fig.…”
Section: How Is Breathing Variability Generated?mentioning
confidence: 86%
“…6B). This principle has been well documented in a variety of invertebrate (Crisp et al, 2012; Dickinson and Nagy, 1983; Khorkova and Golowasch, 2007; Ramirez and Pearson, 1991a,b; Zhao and Golowasch, 2012) and other mammalian networks (Kolaj et al, 2007; Mrejeru et al, 2011; Tsuruyama et al, 2013). Within the respiratory network, multiple neuromodulators, such as serotonin, norepinephrine, acetylcholine, or substance P,can alter the distribution of these activities (Doi and Ramirez, 2008; Ramirez et al, 2012; Fig.…”
Section: How Is Breathing Variability Generated?mentioning
confidence: 86%
“…These actions are a result of a complex modulation of intrinsic cellular properties and synaptic connectivity (for review see Harris-Warrick et al, 1998). Remarkably, in some species dopamine demonstrates the ability to reconfigure circuits or networks to generate completely different motor behaviors (Puhl and Mesce, 2008; Crisp et al, 2012; Puhl et al, 2012). More recent studies have highlighted the ability of dopamine to shape a motor network during development, producing a change in motor behaviors from immature to more mature adult-like behaviors (Lambert et al, 2012).…”
Section: Dopamine’s Role In Locomotionmentioning
confidence: 99%
“…Specifically, dopamine acts as a command signal to elicit crawling along with suppression of swimming (Puhl and Mesce, 2008; Crisp et al, 2012; Puhl et al, 2012), and is an excellent example of the ability of dopamine to bias locomotor behavior (Crisp and Mesce, 2004). Dopamine has a similar effect in nematodes (e.g., Caenorhabditis elegans) where it also acts to bias locomotor activity to a crawl pattern of activity over swimming (Vidal-Gadea et al, 2011).…”
Section: Dopamine’s Role In Rhythmicity: Invertebratesmentioning
confidence: 99%
“…Neuromodulation, particularly through biogenic amine pathways, has also been a successful research direction in the leech. By adding dopamine and other pharmacological agents to the nervous system through the saline solution, it has been shown that dopamine modulates neural networks involved in decision-making 23 and motor patterns for crawling behavior 24,25 . This experimental approach is a simple (and inexpensive) way to incorporate modulation into the teaching laboratory, and adjusting the ionic makeup of the saline solution is an effective way to teach the Nernst and Goldman-Hodgkin-Katz equations.…”
Section: Discussionmentioning
confidence: 99%